2022
DOI: 10.9734/cjast/2022/v41i2731785
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Economics of Traditional and Modern Dairy Farms in Eastern U.P.

Abstract: A samples of total 270 dairy respondents were selected from the selected district and purposive cum random sampling technique was adopted for the study. It was observed that over all the categories of sample farm groups selected, the gross total investment was found in decreasing trend at Rs. /Animal i.e., Rs. 1660335.42, Rs. 176674.52 and Rs. 122801.01 for marginal, medium and large category of dairy farms, respectively. Overall Net returns per litre of milk produced were found Rs. 12 on traditional farm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This data recommends that a significant proportion of commercial dairy farmers possess a commendable grasp of these essential practices, indicating a positive trend towards improved efficiency, productivity, and sustainability within the dairy industry. The finding of Kirar et al [2] showed that majority of the dairy farmers (79.17 per cent) had medium level of knowledge regarding improved dairy management practices.…”
Section: Knowledge About Scientific Dairymentioning
confidence: 97%
See 1 more Smart Citation
“…This data recommends that a significant proportion of commercial dairy farmers possess a commendable grasp of these essential practices, indicating a positive trend towards improved efficiency, productivity, and sustainability within the dairy industry. The finding of Kirar et al [2] showed that majority of the dairy farmers (79.17 per cent) had medium level of knowledge regarding improved dairy management practices.…”
Section: Knowledge About Scientific Dairymentioning
confidence: 97%
“…By using a combination of technological innovations and traditional dairy farming practices, dairy farmers in Jabalpur can enhance milk production and quality. The locale is ideal for rearing high-yield dairy cattle breeds due to its fertile soil, abundant water resources, and friendly environment [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%